Farm households’ vulnerability to climate change in Cambodia, Myanmar, and Vietnam: An advanced livelihood vulnerability indexing approach - Minh, Dao Duy; Oo, Aung Tun; Sovanndara, Ky (Asian Journal of Agriculture and Rural Development, 2023)
Southeast Asia is considered one of the world’s climate hotspots as the countries in the Mekong region, in particular, will be the hardest hit by the impacts of climate change if the global temperature continues to rise. This study aims to evaluate the differences in climate change-induced vulnerability of farm households in Cambodia, Vietnam, and Myanmar. The total sample size was 999 farm respondents, of which 304 were from Myanmar, 350 from Vietnam, and 345 from Cambodia. The farm households’ vulnerability was measured using an advanced indicator or indexing method with balanced or equal weighting. A total of 36 indicators were selected based on an extensive literature review and expert judgment. Each major component was comprised of sub-components and indicators, which were standardized using a balanced weighted average approach. The findings reveal that Myanmar was high in all components of climate change vulnerability, whereas Vietnam was the second most vulnerable country, followed by Cambodia. Based on the findings, we suggest implementing policy measures that aim to reduce the sensitivity dimension of farm households, such as by improving early warning systems, increasing public funding investment in infrastructure development, and creating embankments to prevent saltwater incursion, while empowering the adaptive capacity of farm households. Furthermore, we also recommend establishing the necessary healthcare facilities, strengthening the public-private partnership, increasing outreach and healthcare services, and improving access to the formal credit system.